2006
DOI: 10.1111/j.1600-0501.2005.01223.x
|View full text |Cite
|
Sign up to set email alerts
|

Ninety percent success in palatal implants loaded 1 week after placement: a clinical evaluation by resonance frequency analysis

Abstract: To investigate the behaviour of early loaded palatal implants when observed with resonance frequency analysis (RFA). Twenty patients (seven males and 13 females, mean age 26.4 years) received one palatal implant each (length: 4 mm, diameter: 3.3 mm; Orthosystem) for maximum orthodontic anchorage. The implants' stability was observed by RFA. Measurements were carried out at the time of surgery, after first orthodontic loading and subsequently once a week over a period of 12 weeks. Two palatal implants were lost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 26 publications
3
36
0
6
Order By: Relevance
“…Initial clinical data on early loading of palatal implants show success rates ranging from 90% to 100% [4][5] and thus do not differ from the success rates associated with conventionally-loaded palatal implants [1-2, 12-13, 17-18]. However, these data refer to indirect forms of anchorage with orthodontic forces of up to 4 N only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial clinical data on early loading of palatal implants show success rates ranging from 90% to 100% [4][5] and thus do not differ from the success rates associated with conventionally-loaded palatal implants [1-2, 12-13, 17-18]. However, these data refer to indirect forms of anchorage with orthodontic forces of up to 4 N only.…”
Section: Discussionmentioning
confidence: 99%
“…Initial clinical data on this subject focus on the fundamental applicability of early loading in individual indications [4][5]8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditions for early loading on maxillary posterior single implants were set as 50 Ncm and 70 or more ISQ value/ The initial decrease in the ISQ values within the first 3 weeks has been reported in many studies. 19,20 However, ISQ values at the time of surgery and 1 or 2 weeks after surgery were not decreased but stable in this case. This case report is showing a new possibility of loading protocol at the maxillary posterior area with a deep threaded wide implant.…”
Section: 14mentioning
confidence: 62%
“…Three implants failed early; they were lost during the healing phase within 12 weeks after placement. Crismani et al 11) reported a success rate of 90% in their study, in which 20 palatal implants were placed in 20 patients. Bantleon et al…”
Section: Discussionmentioning
confidence: 99%